Revealing Natural Intracellular Peptides in Gills of Seahorse Hippocampus reidi - Correa, Claudia Neves [UNESP]; Fiametti, Louise Oliveira [UNESP]; de Barros, Gabriel Marques [UNESP]; de Castro, Leandro Mantovani [UNESP] (MDPI, 2023)
The seahorse is a marine teleost fish member of the Syngnathidae family that displays a complex variety of morphological and reproductive behavior innovations and has been recognized for its medicinal importance. In the Brazilian ichthyofauna, the seahorse Hippocampus reidi is among the three fish species most used by the population in traditional medicine. In this study, a protocol was performed based on fast heat inactivation of proteases plus liquid chromatography coupled to mass spectrometry to identify native peptides in gills of seahorse H. reidi. The MS/MS spectra obtained from gills allowed the identification of 1080 peptides, of which 1013 peptides were present in all samples and 67 peptide sequences were identified in an additional LC-MS/MS run from an alkylated and reduced pool of samples. The majority of peptides were fragments of the internal region of the amino acid sequence of the precursor proteins (67%), and N- and C-terminal represented 18% and 15%, respectively. Many peptide sequences presented ribosomal proteins, histones and hemoglobin as precursor proteins. In addition, peptide fragments from moronecidin-like protein, described with antimicrobial activity, were found in all gill samples of H. reidi. The identified sequences may reveal new bioactive peptides.
Keywords: mass spectrometry; peptidomics; seahorse